Representing Auschwitz
XIII, 246 p.
Keywords: This collection of essays by leading international scholars takes the Scrolls of Auschwitz as its starting point. These powerful hand-written testimonies, produced within Birkenau, seek to bear witness to mass murder from at its core. The highly literary accounts pose a fundamental challenge to the idea the Holocaust cannot be attested to.